Angiosperm symbioses with non‐mycorrhizal fungal partners enhance N acquisition from ancient organic matter in a warming maritime Antarctic. (17th October 2019) - Hill, Paul W.; Broughton, Richard; Bougoure, Jeremy; Havelange, William; Newsham, Kevin K.; Grant, Helen; Murphy, Daniel V.; Clode, Peta; Ramayah, Soshila; Marsden, Karina A.; Quilliam, Richard S.; Roberts, Paula; et al.
Abstract: In contrast to the situation in plants inhabiting most of the world's ecosystems, mycorrhizal fungi are usually absent from roots of the only two native vascular plant species of maritime Antarctica, Deschampsia antarctica and Colobanthus quitensis . Instead, a range of ascomycete fungi, termed dark septate endophytes (DSEs), frequently colonise the roots of these plant species. We demonstrate that colonisation of Antarctic vascular plants by DSEs facilitates not only the acquisition of organic nitrogen as early protein breakdown products, but also as non‐proteinaceous d ‐amino acids and their short peptides, accumulated in slowly‐decomposing organic matter, such as moss peat. Our findings suggest that, in a warming maritime Antarctic, this symbiosis has a key role in accelerating the replacement of formerly dominant moss communities by vascular plants, and in increasing the rate at which ancient carbon stores laid down as moss peat over centuries or millennia are returned to the atmosphere as CO2 . Abstract : In contrast to the situation in plants inhabiting most of the world's ecosystems, mycorrhizal fungi are usually absent from roots of the only two native vascular plant species of maritime Antarctica, Deschampsia antarctica and Colobanthus quitensis. Instead, a range of ascomycete fungi, termed dark septate endophytes (DSEs), frequently colonise the roots of these plant species. We demonstrate that colonisation of Antarctic vascular plants by DSEs facilitates not only the acquisition of organic nitrogen as early protein breakdown products, but also as non‐proteinaceous D‐amino acids and their short peptides, accumulated in slowly‐decomposing organic matter, such as moss peat.